2015
DOI: 10.2337/db15-0764
|View full text |Cite
|
Sign up to set email alerts
|

Antiaging Glycopeptide Protects Human Islets Against Tacrolimus-Related Injury and Facilitates Engraftment in Mice

Abstract: Clinical islet transplantation has become an established treatment modality for selected patients with type 1 diabetes. However, a large proportion of transplanted islets is lost through multiple factors, including immunosuppressant-related toxicity, often requiring more than one donor to achieve insulin independence. On the basis of the cytoprotective capabilities of antifreeze proteins (AFPs), we hypothesized that supplementation of islets with synthetic AFP analog antiaging glycopeptide (AAGP) would enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Gala-Lopez et al found that an anti-aging glycopeptide (AAGP) protected human islets from tacrolimus toxicity and promoted graft survival and function. 133 Ongoing work in the area of tolerance induction using myeloablative chemotherapy or nonablative cellular therapeutics including facilitating cells or Tregs could transform future opportunities across all aread of transplantation.…”
Section: Post-transplant Limitationsmentioning
confidence: 99%
“…Gala-Lopez et al found that an anti-aging glycopeptide (AAGP) protected human islets from tacrolimus toxicity and promoted graft survival and function. 133 Ongoing work in the area of tolerance induction using myeloablative chemotherapy or nonablative cellular therapeutics including facilitating cells or Tregs could transform future opportunities across all aread of transplantation.…”
Section: Post-transplant Limitationsmentioning
confidence: 99%
“…It is widely believed that NODAT is caused by exposure to steroids or high dose calcineurin inhibitors, including tacrolimus (TAC; also known as FK506) and cyclosporin (CsA) (1,2). These drugs are shown to damage cell types critical for the maintenance of glucose homeostasis, particularly pancreatic b-cells (3). TAC is a mainstay for prevention of transplant rejection, but effective immunosuppression targeting a concentration range of 4-11 ng/mL still results in NODAT in > 20% of patients (1).…”
Section: Introductionmentioning
confidence: 99%
“…But tacrolimus is also shown not to cause significant apoptosis in beta-cells [ 6 , 39 ], which correlates well with our findings of no increase in cell death following tacrolimus exposure. Short time exposure of tacrolimus has recently been shown to highly suppress insulin secretion in human islets without changing intracellular insulin content or viability [ 40 ]. This is consistent with our study ( Figure 1(c) ) and others [ 6 , 39 ].…”
Section: Discussionmentioning
confidence: 99%